Evaluation of Cable Tension Using Static and Dynamic Test on R.H. Fisabilillah Cable-Stayed Bridge, Batam-Indonesia - Santoso, Hinawan Teguh; Hidayat, Irfan (Universitas Negeri Semarang, 2023)
R.H. Bridge Fisabilillah (Bridge I) is a cable-stayed bridge, included in the series of Barelang Bridges (Batam-Rempang-Galang) which were built from 1992 to 1998. With the service life of the bridge reaching 25 years, it is necessary to check the health condition of the bridge structure. Bridge cables are one of the most important elements of a cable-stayed bridge. These cable elements dominantly experience tensile forces when transmitting loads from the decks to the bridge pylons. Cable force inspection methods can be carried out through the direct measurement method (e.g. static test using a lift-off method) and indirect measurement (e.g. dynamic test using accelerometer sensors, electromagnetic/EM sensors, and so on). This study aims to compare the cable tensile force based on the static test (lift-off method) in 2017 against the dynamic test (accelerometer sensors) in 2022. Evaluation of the cable tensile force based on the dynamic test was carried out using the taut string theory and beam string theory approaches. From the study, the two empirical approaches yielded insignificantly different results where a difference in the mean difference of -1,71% was found with a maximum difference of 28,15%. The study also shows an increase in cable force capacity to a maximum of 47,20% UTS (ultimate tensile strength) based on the taut string theory and a maximum of 53.37% UTS based on the beam string theory. This value is greater when compared to the results of the cable force based on the static test (lift-off) in 2017, which was a maximum of 41.64% UTS. It is recommended to carry out further and more comprehensive studies to determine the effect of changes in cable force distribution on the behavior of the structure on the R.H. Fisabilillah Bridge.